Mental Health Outcomes Associated with Risk and Resilience among Military‐Connected Youth. Issue 2 (27th September 2020) - Sullivan, Kathrine S.; Hawkins, Stacy Ann; Gilreath, Tamika D.; Castro, Carl A.
Abstract : The present study aimed to describe patterns of risk and protective factors affecting U.S. Army families and their association with mental health diagnoses among military‐connected children. Wartime military service is associated with increased adverse outcomes for military‐connected youth, but few studies have explored the impact of concurrent risk and access to protective factors. Using big data methods to link existing datasets, protective factors (e.g., marital and family functioning) were drawn from a voluntary survey completed by 1, 630 US Army spouses. Risk factors (e.g., parent mental health, family moves, deployment) were drawn from Department of Defense (DoD) archival data. Rates of mental health diagnoses among youth were derived from DoD healthcare records. Using the three‐step method of latent profile analysis, five profiles emerged with variability across risk and protective factors. The largest group (40% of the sample) had considerable protective factors and limited risk exposure. Statistically significant differences in the prevalence of mental health diagnoses among military‐connected youth were observed across profiles (χ 2 = 30.067, df = 4, p < .001), with the highest rates (31.1% and 30.5%) observed in the two profiles with the lowest protective factors. Findings suggest most military families are faring well and highlight the importance of a thorough assessment that evaluates both the stressors military families face and the strengths they possess. Resumen: el presente estudio tuvo como finalidad describir los patrones de riesgo y los factores protectores que afectan a las familias del Ejército de los Estados Unidos y su asociación con los diagnósticos de salud mental entre niños relacionados con los militares. El servicio militar en tiempos de guerra está asociado con mayores consecuencias adversas para los jóvenes relacionados con los militares, pero pocos estudios han analizado el efecto del riesgo simultáneo y el acceso a los factores protectores. Utilizando métodos de datos masivos para conectar conjuntos de datos existentes, se extrajeron los factores protectores (p. ej.: funcionamiento familiar y conyugal) de una encuesta voluntaria contestada por 1630 cónyuges de militares del Ejército de los Estados Unidos. Los factores de riesgo (p. ej.: la salud mental de los padres, las mudanzas familiares, las comisiones) se obtuvieron de los datos de archivo del Departamento de Defensa (DoD). Los índices de los diagnósticos de salud mental entre los jóvenes se extrajeron de los expedientes de asistencia sanitaria del DoD. Utilizando el método de tres pasos del análisis de perfiles latentes, surgieron cinco perfiles con variabilidad entre los factores de riesgo y los factores protectores. El grupo más grande (el 40% de la muestra) tuvo factores protectores considerables y una exposición a riesgos limitada. Se observaron diferencias estadísticamente significativas en la prevalencia de diagnósticos de salud mental entre los jóvenes relacionados con los militares en los perfiles (χ 2 = 30.067, df = 4, p < .001), y los índices más altos (31.1% and 30.5%) se observaron en los 2 perfiles con factores protectores más bajos.Los resultados sugieren que la mayoría de las familias militares se encuentran bien y destacan la importancia de una evaluación exhaustiva que evalúe tanto los factores desencadenantes de estrés que enfrentan las familias de militares como las fortalezas que poseen. 摘要: 本研究旨在描述影响美国军人家庭的风险模式和保护性因素，以及与部队相关联的青少年其心理健康诊断的相关性。战时服兵役与很多和部队相关联青少年其不良后果有所增加有关，但很少有研究探讨两者同时出现的风险和获得保护因素的影响。使用大数据方法连接现有的数据集，保护因素(如婚姻和家庭功能)是从1630名美国军人配偶完成的自愿调查中得出的。风险因素(如父母心理健康、家庭迁移、部署)取自美国国防部(DoD)档案数据。青少年的精神健康诊断率来自于国防部的医疗记录。采用分三步的潜在剖面分析方法，得到了5个具有不同风险和保护因素的剖面。最大的一组(40%的样本)有相当多的保护因素和有限的风险暴露。通过对不同的剖面观察分析得到，与部队相关联的年轻人其心理健康诊断的普遍存在性在统计上有显著差异 (χ2 = 30.067, df = 4, p < .001)，其中最高的比率(31.1%及30.5%)出现在2个防护因数最低的剖面上。调查结果表明，大多数军人家庭情况都不错，并强调了一种全面评估量表的重要性，这种量表可以评估军人家庭面临的压力和他们拥有的优势。